Domesticating Vigna stipulacea: Chromosome-Level genome assembly reveals VsPSAT1 as a candidate gene decreasing hard-seededness - Takahashi, Yu; Sakai, Hiroaki; Ariga, Hirotaka; Teramoto, Shota; Shimada, Takashi L.; Eun, Heesoo; Muto, Chiaki; Naito, Ken; Tomooka, Norihiko (Frontiers in Plant Science, 2023)
To increase food production under the challenges presented by global climate change, the concept of de novo domestication—utilizing stress-tolerant wild species as new crops—has recently gained considerable attention. We had previously identified mutants with desired domestication traits in a mutagenized population of the legume Vigna stipulacea Kuntze (minni payaru) as a pilot for de novo domestication. Given that there are multiple stress-tolerant wild legume species, it is important to establish efficient domestication processes using reverse genetics and identify the genes responsible for domestication traits. In this study, we identified VsPSAT1 as the candidate gene responsible for decreased hard-seededness, using a Vigna stipulacea isi2 mutant that takes up water from the lens groove. Scanning electron microscopy and computed tomography revealed that the isi2 mutant has lesser honeycomb-like wax sealing the lens groove than the wild-type, and takes up water from the lens groove. We also identified the pleiotropic effects of the isi2 mutant: accelerating leaf senescence, increasing seed size, and decreasing numbers of seeds per pod. While doing so, we produced a V. stipulacea whole-genome assembly of 441 Mbp in 11 chromosomes and 30,963 annotated protein-coding sequences. This study highlights the importance of wild legumes, especially those of the genus Vigna with pre-existing tolerance to biotic and abiotic stresses, for global food security during climate change.